Visualizing Basketball's Past: The Historical Imagination of ESPN's Basketball Documentaries. (December 2017) - Colás, Yago
ESPN's 22 basketball-themed documentaries are popular and influential sources for students and fans interested in basketball history. I offer close readings of two films, There's No Place Like Home and The Fab Five, to shed light on how they (and to some degree the corpus as a whole) portray basketball history, reflect on the historiographical task of portraying the past, and affectively engage viewers to adopt certain stances with respect to the past and its portrayal. There's No Place Like Home invites viewers to share in a fantasy of basketball as a decontextualized static idea whose history can be possessed. By contrast, The Fab Five challenges viewers to view basketball history as contested terrain where conflicting power vectors of language, culture, and society intersect.